2013
DOI: 10.1016/j.eurger.2013.06.005
|View full text |Cite
|
Sign up to set email alerts
|

An alternative method for Frailty Index cut-off points to define frailty categories

Abstract: Purpose the Frailty Index (FI) is a popular operationalization of frailty. FI cut-off points have been proposed to define, regardless of age, frailty categories with increasing risk. Here, an alternative method is described that takes age into account. Subjects and methods 29,905 participants aged ≥ 50 from the first wave of the Survey of Health, Ageing and Retirement in Europe. The mean follow-up for mortality was 2.4 years. Curve estimation procedures were carried out between age and a FI, and 50% Confiden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
29
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(32 citation statements)
references
References 29 publications
2
29
1
Order By: Relevance
“…Some deficits, namely the psychological variables and ADL deficits, had a low frequency in the selected cohort, thus contributing little to the index overall, but it was decided to retain them to maintain consistency within the index for its future application to cognitively impaired participants in the cohort in whom these variables become more prevalent. Also, use of the Frailty Index cut‐points may not be relevant to this population; evaluating age‐specific reference ranges may be more appropriate for future studies in which there are more participants across the age ranges that would allow for greater precision . Nevertheless, when further analyses were conducted using quartiles of the Frailty Index in this population, the results were similar.…”
Section: Discussionmentioning
confidence: 87%
“…Some deficits, namely the psychological variables and ADL deficits, had a low frequency in the selected cohort, thus contributing little to the index overall, but it was decided to retain them to maintain consistency within the index for its future application to cognitively impaired participants in the cohort in whom these variables become more prevalent. Also, use of the Frailty Index cut‐points may not be relevant to this population; evaluating age‐specific reference ranges may be more appropriate for future studies in which there are more participants across the age ranges that would allow for greater precision . Nevertheless, when further analyses were conducted using quartiles of the Frailty Index in this population, the results were similar.…”
Section: Discussionmentioning
confidence: 87%
“…We do know that there is an association between age and FI, in that it is increased in older age groups, but because the variance explained by age is small, it is debatable if categorizing frailty accounting for age will make a difference. 34 The prevalence of frailty in this study was 5.7%, and 61.8% of the respondents were prefrail. The National Health and Nutritional Examination Survey (NHANES) reported that there were 30% of frail elders and 34% in the vulnerable category.…”
Section: Discussionmentioning
confidence: 97%
“… 74 In addition, an age-adjusted method for frailty screening may be more sensitive in younger ages and more specific in older ages, benefiting the purpose of population screening. 75 The continuous, age-adjusted SHARE-FI75+ score values range from 0 to 1, making it a much more intuitive score than the age-unadjusted one given by SHARE-FI (−4 to 6). 32 …”
Section: Discussionmentioning
confidence: 99%